In silico analysis of candidate proteins sharing homology with Streptococcus agalactiae proteins and their role in male infertility. (2nd January 2017) - Parida, Rajeshwari; Samanta, Luna
ABSTRACT: Leukocytospermia is a physiologic condition defined as human semen with a leukocyte count of >1 x 10 6 cells/ml that is often correlated with male infertility. Moreover, bacteriospermia has been associated with leukocytospermia ultimately leading to male infertility. We have found that semen samples with >1 x 10 6 /ml leukocytes and/or bacteriospermia have oxidative predominance as evidenced by augmented protein carbonyl and lipid peroxidation status of the semen which is implicated in sperm dysfunction. It has been reported that Streptococcus agalactiae is present in bacteriospermic samples. Previous research has shown that human leukocyte antigen beta chain paralog (HLA-DRB) alleles interact best with the infected sperm cells rather than the non-infected cells. Little is known about the interaction of major histocompatibility complex (MHC) present on leukocytes with the sperm upon bacterial infection and how it induces an immunological response which we have addressed by epitope mapping. Therefore, we examined MHC class II derived bacterial peptides which might have human sperm-related functional aspects. Twenty-two S. agalactiae proteins were obtained from PUBMED protein database for our study. Protein sequences with more than two accession numbers were aligned using CLUSTAL Omega to check their conservation pattern. Each protein sequence was then analyzed for T-cell epitope prediction against HLA-DRB alleles using the immune epitope database (IEDB) analysis tool. Out of a plethora of peptides obtained from this analysis, peptides corresponding to proteins of interest such as DNA binding response regulator, hyaluronate lyase and laminin binding protein were screened against the human proteome using Blastp. Interestingly, we have found bacterial peptides sharing homology with human peptides deciphering some of the important sperm functions. Antibodies raised against these probable bacterial antigens of fertility will not only help us understand the mechanism of leukocytospermia/bacteriospermia induced male factor infertility but also open new avenues for immunocontraception. Abbreviations : AA: amino acid; ASA: antisperm antibodies; GBS: group B streptococcus; HLA: human leukocyte antigen; HAS3: hyaluronan synthase 3: IEDB: immune epitope database; MAPO2: O 6 –methylguanine–induced apoptosis 2; MHC: major histocompatibility complex; ROS: reactive oxygen species; Rosbin1: round spermatid basic protein 1; S. agalactiae: Streptococcus agalactiae; SA: sperm antigen; SPATA17: spermatogenesis associated protein17; SPNR: spermatid perinuclear RNA binding protein; TEX15: testis-expressed sequence 15 protein; TOPAZ: testis– and ovary-specific PAZ domain–containing protein; TPABP: testis-specific poly–A binding protein; TPAP: testis–specific poly(A) polymerase; WHO: World Health Organization